Community structure of Echinoderms in seagrass beds of Pacitan beaches, East Java, Indonesia - FARID KAMAL MUZAKI; EDWIN SETIAWAN; GHULAM FATHIR AUTHAR INSANY; NURUL KUSUMA DEWI; IWENDA BELLA SUBAGIO (Society for Indonesian Biodiversity, 2019)
Abstract. Muzaki FK, Setiawan E, Insany GFA, Dewi NK, Subagio IB. 2019. Community structure of Echinoderms in seagrass beds of Pacitan beaches, East Java, Indonesia. Biodiversitas 20: 1787-1793. In this study, we attempt to access diversity and community structure of Echinoderms on seagrass beds in each three belt transect (width 2 m, length 100 m) in Tawang and Pidakan beaches, Pacitan, East Java, Java. Observed parameters were species richness, composition, and abundance, as well as diversity indices: Shannon-Wiener's diversity index (H'), Simpson's dominance index (D) and Pielou's evenness index (J). At the end of the study, we identified one species of sea star (Asteroidea), seven species of brittle stars (Ophiuroidea), ten species of sea cucumbers (Holothuroidea) andnine species of sea urchins (Echinoidea). The most dominant species were Ophiocoma dentata (F. Ophiocomidae), Diadema setosum (F. Diadematiidae), Ophiomastix annulosa (F. Ophiocomidae) and Echinometra mathaei (F. Echinometridae). Value of H’ ranged from 0.538 to 1.252 in Tawang and 1.041 to 1.704 in Pidakan; which showing higher species richness and diversity in Pidakan. Echinoderm in the study area was not evenly distributed; D. setosum was very dominant in Tawang beach, while those three other species were more common in Pidakan. Furthermore, most of Holothuroid and Ophiuroid were found only in Pidakan which have relatively more complex habitat.